Man of the frontier - Eason, Breezy, 1886-1956; Autry, Gene, 1907-1998; McGowan, Stuart; McGowan, Dorrell; Republic Pictures Corporation; Cinetel Films ([Los Angeles, CA] : Republic Pictures Corp, 1936)
Gene and Frog set out to find out who has been causing the accidents at a dam construction site. --
Originally released as a motion picture in 1936.
Gene Autry, Smiley Burnette, Frances Grant, Boothe Howard, Jack Kennedy, Champion.
Cinematographer, William Nobles; editor, Carl Pierson.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed December 4, 2015).
Keywords: Water rights -- West (U.S.) -- Drama; Bankers -- West (U.S.) -- Drama; Hoover Dam (Ariz. and Nev.); Country music -- To 1951.; Western films; Feature films; Internet videos; Short films; Streaming video